Genetic Dissection of Internode Length Above the Uppermost Ear in Four RIL Populations of Maize (Zea mays L.). Issue 2 (1st February 2015) - Ku, Lixia; Cao, Liru; Wei, Xiaomin; Su, Huihui; Tian, Zhiqiang; Guo, Shulei; Zhang, Liangkun; Ren, Zhenzhen; Wang, Xiaobo; Zhu, Yuguang; Li, Guohui; Wang, Zhiyong; et al.
Abstract: The internode length above the uppermost ear (ILAU) is an important influencing factor for canopy architecture in maize. Analyzing the genetic characteristics of internode length is critical for improving plant population structure and increasing photosynthetic efficiency. However, the genetic control of ILAU has not been determined. In this study, quantitative trait loci (QTL) for internode length at five positions above the uppermost ear were identified using four sets of recombinant inbred line (RIL) populations in three environments. Genetic maps and initial QTL were integrated using meta-analyses across the four populations. Seventy QTL were identified: 16 in population 1; 14 in population 2; 25 in population 3; and 15 in population 4. Individual effects ranged from 5.36% to 26.85% of phenotypic variation, with 27 QTL >10%. In addition, the following common QTL were identified across two populations: one common QTL for the internode length of all five positions; one common QTL for the internode length of three positions; and one common QTL for the internode length of one position. In addition, four common QTL for the internode length of four positions were identified in one population. The results indicated that the ILAU at different positions above the uppermost ear could be affected by one or several of the same QTL. The traits may also be regulated by many different QTL. Of the 70 initial QTL, 46 were integrated in 14 meta-QTL (mQTLs) by meta-analysis, and 17 of the 27 initial QTL with R 2 >10% were integrated in 7 mQTLs. Four of the key mQTLs (mQTL2-2, mQTL3-2, mQTL5-1, mQTL5-2, and mQTL9) in which the initial QTL displayed R 2 >10% included four to 11 initial QTL for an internode length of four to five positions from one or two populations. These results may provide useful information for marker-assisted selection to improve canopy architecture.